STRA6 Polymorphisms Are Associated With EGFR Mutations in Locally-Advanced and Metastatic Non-Small Cell Lung Cancer Patients - Muñiz-Hernández, Saé; Velázquez-Fernández, Jesús Bernardino; Díaz-Chávez, José; Mondragón-Fonseca, Omar; Mayén-Lobo, Yerye; Ortega, Alberto; López-López, Marisol; Arrieta, Oscar (Frontiers in Oncology, 2020)
Retinol plays a significant role in several physiological processes through their nuclear receptors, whose expression depends on retinol cytoplasmic concentration. Loss of expression of nuclear receptors and low retinol levels have been correlated with lung cancer development. STRA6 is the only described cell membrane receptor for retinol uptake. Some chronic diseases have been linked with specific polymorphisms in STRA6. This study aimed to evaluate four STRA6 single nucleotide polymorphisms (SNPs) (rs4886578, rs736118, rs351224, and rs97445) among 196 patients with locally-advanced and metastatic non-small cell lung cancer (NSCLC) patients. Genotyping, through a validated SNP assay and determined using real time-PCR, was correlated with clinical features and outcomes. NSCLC patients with a TT SNP rs4886578 and rs736118 genotype were more likely to be >60 years, non-smokers, and harboring EGFR mutations. Patients with a TT genotype compared with a CC/CT SNP rs974456 genotype had a median progression-free survival (PFS) of 3.2 vs. 4.8 months, p=0.044, 95% CI) under a platinum-based regimen in the first-line. Furthermore, patients with a TT rs351224 genotype showed a prolonged overall survival (OS), 47.5 months vs. 32.0 months, p= 0.156. This study showed a correlation between clinical characteristics, such as age, non-smoking history, and EGFR mutational status and oncological outcomes depending on STRA6 SNPs. The STRA6 TT genotype SNP rs4886578 and rs736118 might be potential biomarkers in locally-advanced and metastatic NSCLC patients.